Preserving Indonesia's Unity Through The Law Based On Bhineka Tunggal Ika - Soeleman Djaiz Baranyanan; Muhammad Irham; Iqbal Taufik; Hendrik Salmon; Sherlock Halmes Lekipiouw (Faculty of Law, Universitas Pekalongan, 2025)
Based on positive law, which applies in Indonesia,decentralization has